Biometrics studies of caste development in Nasutitermes coxipoensis (Isoptera; Termitidae) - Buschini, MLT; Leonardo, AMC (California State University, 2002)
A biometric study of caste development was carried out using Nasutitermes sp., by measuring the height, width, and length of the head, the length and width of the pronotum and mesonotum, and the length of the posterior tibia. These measurements were taken on 200 individuals, including larvae, nymphs, workers, pre-soldiers and soldiers. For instar separation, it was verified that the Principal Component Analysis (P.C.A.) was the most efficient methodology. Results of this analysis showed that Nasutitermes coxipoensis follows the general pattern of development presented by other Nasutitermes.
Keywords: Insecta; Isoptera; Nasutitermes; caste; development